Decision-Making Ability: A Missing Link Between Health Literacy, Contextual Factors, and Health - René Rüegg (Health Literacy Research and Practice, 2022)
Background: Health literacy has often been described as an important precondition for good health decisions, healthy behaviors, and health. However, reviews reveal low evidence for intervention effectiveness through health literacy. This result calls for more investigations to be done in the pathway from health literacy to health, considering intermediate outcomes of health literacy. Objective: This study explores an important immediate objective of health literacy, namely the decision-making ability (DMA) regarding health issues. The study's hypothesis claims the DMA to be an important mediator between health literacy and health outcomes. Furthermore, the study assumes that the effect of the DMA on different health outcomes is not only contingent on health literacy but also on contextual factors. To test the above hypotheses, six different health literacy dimensions and four health outcomes have been analyzed. Methods: Cross-sectional data from the Young Adult Survey Switzerland was used for mediation analyses (N = 4, 569, age, 18 to 25 years, all male). Multiple regression and KHB (Karlson, Holm, and Breen) decomposition analyses were applied to estimate mediation effects between health literacy and health outcomes. Key Results: Five of six health literacy dimensions explained the DMA in a linear regression model. The coefficients of the DMA explaining health outcomes were substantially reduced when health literacy items were included into the models (6.1%–20.3%). Furthermore, the associations between health literacy and the health outcomes were fully explained by contextual factors, except in the mental health model. Conclusions: The results support the hypothesis that higher health literacy levels do not necessarily lead to better health directly. Rather, health literacy is just one of multiple factors contributing to a higher DMA and, further, to favorable health outcomes. The results of this study call for more investigations in the health decision-making process and the role of contextual factors. [HLRP: Health Literacy Research and Practice. 2022;6(3):e213–e223.] Plain Language Summary: The study investigated the ability to make good health decisions while considering health literacy. The results support the intermediate function of the decision-making ability on the path to favorable health outcomes. Furthermore, it is found that the DMA as well as health literacy are highly contingent on contextual factors. The results shed light into the complex decision-making process regarding health issues.